Using the Intervention Mapping protocol to develop a family-based intervention for improving lifestyle habits among overweight and obese children: study protocol for a quasi-experimental trial - Tonje Holte Stea; Tommy Haugen; Sveinung Berntsen; Vigdis Guttormsen; Nina Cecilie Øverby; Kristin Haraldstad; Eivind Meland; Eirik Abildsnes (BMC Public Health, 2016)
Abstract Background In light of the high prevalence of childhood overweight and obesity, there is a need of developing effective prevention programs to address the rising prevalence and the concomitant health consequences. The main aim of the present study is to systematically develop and implement a tailored family-based intervention for improving lifestyle habits among overweight and obese children, aged 6–10 years old, enhancing parental self-efficacy, family engagement and parent-child interaction. A subsidiary aim of the intervention study is to reduce the prevalence of overweight and obesity among those participating in the intervention study. Methods/design The Intervention Mapping protocol was used to develop a tailored family-based intervention for improving lifestyle habits among overweight and obese children. In order to gather information on local opportunities and barriers, interviews with key stakeholders and a 1-year pilot study was conducted. The main study has used a quasi-experimental controlled design. Locally based Healthy Life Centers and Public Health Clinics are responsible for recruiting families and conducting the intervention. The effect of the study will be measured both at completion of the 6 months intervention study and 6 and 18 months after the intervention period. An ecological approach was used as a basis for developing the intervention. The behavioral models and educational strategies include individual family counselling meetings, workshops focusing on regulation of family life, nutrition courses, and physical activity groups providing tailored information and practical learning sessions. Parents will be educated on how to use these strategies at home, to further support their children in improving their behaviors. Discussion A systematic and evidence-based approach was used for development of this family-based intervention study targeting overweight and obese children, 6–10 years old. This program, if feasible and effective, may be adjusted to local contexts and implemented in all municipal health care institutions in Norway. Trial registration NCT02247219 . Prospectively registered on October 26, 2014.